2003
DOI: 10.1104/pp.103.029249
|View full text |Cite
|
Sign up to set email alerts
|

The Sulfolipids 2′-O-Acyl-Sulfoquinovosyldiacylglycerol and Sulfoquinovosyldiacylglycerol Are Absent from aChlamydomonas reinhardtiiMutant Deleted inSQD1 

Abstract: The biosynthesis of thylakoid lipids in eukaryotic photosynthetic organisms often involves enzymes in the endoplasmic reticulum (ER) and the chloroplast envelopes. Two pathways of thylakoid lipid biosynthesis, the ER and the plastid pathways, are present in parallel in many species, including Arabidopsis, but in other plants, e.g. grasses, only the ER pathway is active. The unicellular alga Chlamydomonas reinhardtii diverges from plants like Arabidopsis in a different way because its membranes do not contain p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(66 citation statements)
references
References 29 publications
6
57
2
Order By: Relevance
“…While monoglycerides and triglycerides were not affected significantly, there was a reduction in the abundance of total DG in lines GPD3-OE1 and GPD3-OE3 compared with the wild type in low-P conditions. The abundance of phospholipids in wild-type C. reinhardtii was reduced in response to P starvation, as observed previously (Riekhof et al, 2003), although this reduction was less pronounced for total phosphatidylethanolamine in the GPD3-OE lines, yet there were no significant differences in phosphatidylethanolamine abundance in comparison with the wild type. The phosphatidylinositol profile also was mostly unchanged between strains, but there was a reduction in the abundance of total phosphatidylinositol in the GPD3-OE3 line in high-P medium.…”
Section: Gpd2 and Gpd3 Overexpression Lines Show Distinct Growth Phensupporting
confidence: 61%
See 1 more Smart Citation
“…While monoglycerides and triglycerides were not affected significantly, there was a reduction in the abundance of total DG in lines GPD3-OE1 and GPD3-OE3 compared with the wild type in low-P conditions. The abundance of phospholipids in wild-type C. reinhardtii was reduced in response to P starvation, as observed previously (Riekhof et al, 2003), although this reduction was less pronounced for total phosphatidylethanolamine in the GPD3-OE lines, yet there were no significant differences in phosphatidylethanolamine abundance in comparison with the wild type. The phosphatidylinositol profile also was mostly unchanged between strains, but there was a reduction in the abundance of total phosphatidylinositol in the GPD3-OE3 line in high-P medium.…”
Section: Gpd2 and Gpd3 Overexpression Lines Show Distinct Growth Phensupporting
confidence: 61%
“…PG is synthesized from PA through the action of enzymes including phosphatidylglycerophosphate synthase (PGPS). Two PGPS gene isoforms in C. reinhardtii are down-regulated during P starvation (Hung et al, 2015), presumably as part of the strategy to compensate for low P availability by reducing phospholipid biosynthesis (Riekhof et al, 2003). Thus, in the GPD3-OE cells, despite increased PA synthesis, if PGPS activity is repressed, PG content will not increase.…”
Section: Discussionmentioning
confidence: 99%
“…Induced accumulation of SQDG upon P limitation has been reported from various organisms including Arabidopsis (Benning and Ohta 2005;Härtel et al 2000;Jouhet et al 2004), rice (Okazaki et al 2013), Chlamydomonas (Riekhof et al 2003), and bacteria (Benning et al 1993;Güler et al 1996). The current study revealed that in soybean leaves, the SQDG content was To investigate the effect of P limitation on the total level of each lipid class in the leaves of the same growth stage, relative intensity of each lipid signal of the same lipid class in Figure 3 was summed and represented in this figure.…”
Section: Copyright © 2017 the Japanese Society For Plant Cell And Molmentioning
confidence: 99%
“…P-starved cells induce high-affinity Pi uptake ) and synthesize extracellular phosphatases (Quisel et al 1996) that enhance Pi scavenging from the environment. Polyphosphate stores (Hebeler et al 1992;Werner et al 2007) and chloroplast DNA (Yehudai-Resheff et al 2007) are also mobilized, and phospholipids are replaced by galactolipids and sulfolipids (Riekhof et al 2003) as cells redistribute their internal P resources. P-starved cells also conserve Pi by inhibiting the turnover of chloroplast transcripts by the phosphorylytic chloroplast polynucleotide phosphorylase (Yehudai-Resheff et al 2007).…”
Section: àmentioning
confidence: 99%